Dietary Intake of Protein by Food Source and Incident Hypertension Among Diverse US Adults: The MESA Study - Ji Yun Tark; Ruosha Li; Bing Yu; Alexis C. Wood; Nikhil S. Padhye; Marcia C. de Oliveira Otto (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Dietary guidelines recommend adequate protein intake from diverse sources for optimal blood pressure; however, its role in hypertension risk remains unclear. We examined prospective associations of protein intake and diversity, overall and by source, with hypertension risk in the MESA (Multi‐Ethnic Study of Atherosclerosis) study. Methods and Results Among 2294 participants aged 45 to 84 years without hypertension at baseline, total, animal, and plant protein intake was assessed using a 120‐item food frequency questionnaire. Protein diversity was evaluated using count and the dissimilarity index. Over a 9‐year median follow‐up, 1356 hypertension cases were identified through blood pressure measurements and medication records. Associations with hypertension risk were assessed using Cox proportional hazards models and restricted cubic spline analyses. In multivariable‐adjusted models, we found inverse, nonlinear relationships between plant protein intake and count (P‐nonlinearity<0.05), indicating a lower hypertension risk associated with higher consumption and number of different plant protein sources. Greater dissimilarity in plant foods was associated with a higher hypertension risk (hazard ratio [HR], 1.72 [95% CI, 1.06–2.81]). We found no statistically significant associations between total or animal protein (intake or diversity in food sources) and risk of hypertension (HRs for each 20 g/d, 1.05 [95% CI, 0.97–1.14]; and 1.06 [95% CI, 0.99–1.15] for total and animal protein intake, respectively). Conclusions These findings suggest that higher consumption and variety of minimally processed plant proteins lower hypertension risk, while minimally processed animal proteins can be included without significantly increasing hypertension risk among middle‐aged US adults.